The Barriers to Developing Students' Scientific Literacy in Learning Physics of Quantities and Measurements - Joko Siswanto*; Suyidno Suyidno; Saiyidah Mahtari; Fitriyani Fitriyani; Winda Febriani; Era Sari (Universitas Syiah Kuala, 2023)
Teaching scientific literacy in schools is not easy, even though it is needed in education in the industrial era 4.0. This study aims to analyze the level of students' scientific literacy skills and their obstacles in school. This research was conducted on tenth graders at two Banjarmasin High Schools, namely SMA which applied the driving curriculum, and SMA which applied the 2013 curriculum. The number of research samples was 60 students who were taken using cluster random sampling. The results of the analysis show students' ability to explain phenomena scientifically, design and evaluate scientific inquiries, and interpret scientific data and evidence in each school in poor criteria (value 40), except to explain phenomena scientifically in group 1 in fairly good criteria (value = 52). The existence of obstacles is believed to interfere with student's ability to understand scientific literacy. These barriers are sourced from students' internal factors (STEM understanding, scientific processes) and are exacerbated by external factors (teachers' STEM literacy, learning atmosphere, infrastructure, assessment, and evaluation).